Synthesis of new conjugated diynes containing carbamate groups, and study of their properties - Vyazmin, Sergey; Berezina, S. E.; Remizova, L. A.; Domnin, I. N.; Gleiter, Rolf (Russian journal of organic chemistry, 2002)
Carbamates of monoacetylene and diacetylene series were synthesized and characterized. A catalytic system CuI-pyrrolidine was applied for the first time to a synthesis of symmetrical diacetylenes by oxidative dimerization of terminal acetylenes. The comparative activity of diynes obtained was studied in the photoinitiated solid-phase topochemical polymerization. Diyne carbamates undergoing thermal polymerization were obtained for the first time.
Gesehen am 11.11.2020